Implementasi Peraturan Presiden Nomor 112 Tahun 2007 Tentang Penataan Pasar Tradisional Ditinjau Dari Perspektif Fiqih Siyasah (Studi Di Pasar Sibuhuan Kabupaten Padang Lawas) - Ikhwanuddin Harahap, Alvin Ramadhy Siregar & Muhammad Arsad Nasution & (Jurnal El-Thawalib, 2020)
The problem in this study is how far the implementation of Presidential Regulation Number 112 of 2007 concerning the Arrangement of Traditional Markets in Sibuhuan Market, Padang Lawas Regency. Because some traders do not implement regulations maximally, and do not comply with existing regulations. The purpose of this study is to describe and analyze the implementation of Presidential Regulation Number 112 of 2007 concerning Traditional Market Arrangement in Sibuhuan Market, Padang Lawas Regency. The author raises the problem formulation, namely How the implementation of traditional market arrangement in Sibuhuan Market, what are the inhibiting factors for the implementation of traditional market arrangement in Sibuhuan Market and How is the fiqhsiyasah review of the implementation of traditional market arrangement in Sibuhuan, Padang Lawas Regency.